Pengaruh Harga Minyak Dunia, Nilai Tukar, Inflasi, Suku Bunga SBI, Indeks Dow Jones, dan Indeks Nikkei 225 terhadap Indeks Sektor Pertambangan yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2011-2017 - SHABRINA MAULINDA, TITA; PURWOHANDOKO, (Jurnal Ilmu Manajemen (JIM), 2018)
This research is to explain the influence of crude oil price, exchange rate, inflation, SBI interest rate, Dow Jones index, and Nikkei 225 index towards mining index in Indonesia Stock Exchange (BEI) period 2011-2017. Data were analyzed by using multiple linear analysis technique and use SPSS 24 as statistical analysis software. The sample type used is saturation samples so that there are 84 data taken monthly from 2011 to 2017. Results of analysis of this study indicate there is a significant negative relationship between inflation and exchange rate towards mining index. Meanwhile Dow jones index has a significant positive relationship towards mining index. The rest variable, crude oil prices, SBI interest rate, and Nikkei 225 index have no significant relationship towards mining index. The implication from this research is that investors should pay more attention to the exchange rate, inflation, and Dow Jones index before investing in mining sector shares.